Integrated metastate functional connectivity networks predict change in symptom severity in clinical high risk for psychosis. Issue 2 (13th October 2020) - Gifford, George; Crossley, Nicolas; Morgan, Sarah; Kempton, Matthew J; Dazzan, Paola; Modinos, Gemma; Azis, Matilda; Samson, Carly; Bonoldi, Ilaria; Quinn, Beverly; Smart, Sophie E; Antoniades, Mathilde; et al.
Abstract: The ability to identify biomarkers of psychosis risk is essential in defining effective preventive measures to potentially circumvent the transition to psychosis. Using samples of people at clinical high risk for psychosis (CHR) and Healthy controls (HC) who were administered a task fMRI paradigm, we used a framework for labelling time windows of fMRI scans as 'integrated' FC networks to provide a granular representation of functional connectivity (FC). Periods of integration were defined using the 'cartographic profile' of time windows and k‐means clustering, and sub‐network discovery was carried out using Network Based Statistics (NBS). There were no network differences between CHR and HC groups. Within the CHR group, using integrated FC networks, we identified a sub‐network negatively associated with longitudinal changes in the severity of psychotic symptoms. This sub‐network comprised brain areas implicated in bottom‐up sensory processing and in integration with motor control, suggesting it may be related to the demands of the fMRI task. These data suggest that extracting integrated FC networks may be useful in the investigation of biomarkers of psychosis risk. Abstract : A framework for extracting epochs of integrated functional connectivity was used to test network differences between healthy control and clinical high‐risk (CHR) groups, as well as associations with longitudinal changes in symptom and functioning scores in CHR participants. A sub‐network suggestive of bottom‐up sensory processing was found to be associated with changes in positive psychotic symptoms in the CHR group. We suggest this to be a useful approach in searching for network‐based biomarkers of psychosis risk.